2004
DOI: 10.1037/1528-3542.4.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Culture Differences in Emotion.

Abstract: In this article, the authors report a secondary analysis on a cross-cultural dataset on gender differences in 6 emotions, collected in 37 countries all over the world. The aim was to test the universality of the gender-specific pattern found in studies with Western respondents, namely that men report more powerful emotions (e.g., anger), whereas women report more powerless emotions (e.g., sadness, fear). The authors expected the strength of these gender differences to depend on women's status and roles in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
262
5
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(300 citation statements)
references
References 19 publications
29
262
5
4
Order By: Relevance
“…Similarly, it has also been found that women tend to report more intense feelings of shame (Ferguson & Eyre, 2000;Fischer et al, 2004).…”
Section: Gender Differences In Emotionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, it has also been found that women tend to report more intense feelings of shame (Ferguson & Eyre, 2000;Fischer et al, 2004).…”
Section: Gender Differences In Emotionmentioning
confidence: 89%
“…They also report more intense negative emotions such as sadness, fear, guilt and shame (Fischer, Rodríguez-Mosquera, van Vianen, & Manstead, 2004). Similarly, it has also been found that women report more intense fear of terrorism (Nellis, 2009).…”
Section: Gender Differences In Emotionmentioning
confidence: 90%
“…In contexts where women are low in social status and power, women are less likely than men to exhibit anger-inspired action intended to confront and fix an aversive situation (e.g., Fischer et al, 2004;Kopper & Epperson, 1996). These gender differences can be understood given a consideration of the nature and function of anger.…”
Section: What Effects Do Patronizing Behaviors Have On Low-power People?mentioning
confidence: 99%
“…The basic equation of "The Hebbian-LMS Learning Algorithm" is as follows [43]: (14) where μ controls stability and convergence speed parameter; Xk is the input pattern; (SUM)k is the sum of inputs; γ is the slope parameter to control the stable equilibrium point; k is the time step. For our spiking neural network based emotional model we have modified the equation of learning weight as follows: (15) where ξ wgt is a coefficient to control stability and convergence speed; γ wgt is a parameter to control the stable equilibrium point; • is "Hadamard Product".…”
Section: Weight Learning By Hebbian-lmsmentioning
confidence: 99%
“…We considered that emotional state varies based on the gender difference [10,14]. Thus, in this paper, the information of gender was taken into consideration as the difference between the parameter of emotion model [20].…”
Section: Distance From Humanmentioning
confidence: 99%